Orientasi Projek Penguatan Profil Pelajar Pancasila dalam Pengembangan Kurikulum Operasional Sekolah Dasar di Papua - Roberto W. Marpaung (Jurnal Pendidikan Indonesia, 2025)
This research was a descriptive research by using quantitative approach. The research was aimed at describing the internalization of Pancasila Student Profiles Project in elementary school curriculum development in Papua Region. The result of the research will be a description and become the real field data of the effectiveness rate of Merdeka Curriculum in elementary school in Papua. Several techniques of data collection used in this research were; interview, observation, and documentation. The result of research showed that the internalization of Pancasila Student profiles development project in the elementary school curriculum development in Papua Region has not effectively been successful. The government needs special research on the relevance of students’ characteristics to the curriculum structure and content. The government has to put the traditional and cultural values on priority when developing school operational curriculum.